2015
DOI: 10.1590/1807-1929/agriambi.v19n11p1042-1048
|View full text |Cite
|
Sign up to set email alerts
|

Canola response to nitrogen sources and split application

Abstract: A B S T R A C TThe aim of this study was to evaluate the response of the canola crop to nitrogen (N) sources and split application. The experiment was carried out in two agricultural years (2009 and 2010), at the experimental unit of the Pontifical Catholic University of Paraná -PUCPR, Campus of Toledo. A completely randomized design in 5 x 2 factorial scheme was adopted in the experiment. The treatments consisted of five split applications of N at sowing and/or as top dressing (0 and 0, 120 and 0, 0 and 120, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…Additionally, physiological investigations have shown that the stem elongation stage is important in the N nutrition of crop when a high N-supply is needed for yield formation (Behrens et al, 2001;Barlo'g and Grzebisz, 2004). Kaefer et al (2015) reported that oilseed rape growth and yield response were not influenced by N fertiliser sources, but were significantly influenced by split N pattern of 1 /3 at sowing and 2 /3 at top-dressing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, physiological investigations have shown that the stem elongation stage is important in the N nutrition of crop when a high N-supply is needed for yield formation (Behrens et al, 2001;Barlo'g and Grzebisz, 2004). Kaefer et al (2015) reported that oilseed rape growth and yield response were not influenced by N fertiliser sources, but were significantly influenced by split N pattern of 1 /3 at sowing and 2 /3 at top-dressing.…”
Section: Discussionmentioning
confidence: 99%
“…At Moorreesburg, nitrogen source had no effect on yield, which may be ascribed to optimum soil N availability and optimum N rates during fertilizer applications (Kaefer et al., 2015). Soil mineral N concentrations ranged between 0.06 and 0.12% from 2016 to 2019 at the site.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, Ercoli et al (2013) found higher nitrogen efficiency with the application of 30 kg ha -1 of the nutrient at the time of sowing and the remainder of the total top dressing dose. In canola, Kaefer et al (2015) observed an increase in the efficiency of nitrogen utilization in the preparation of grains by parceling, with one third at sowing and two thirds at top dressing (40 and 80 kg ha -1 ) applied at the fourth true leaf stage. Due to the supply of nitrogen in top dressing, Mantai et al (2015) state that the maximum efficiency of nitrogen fertilization in oats is obtained with the total dose supplied from 70 to 90 kg ha -1 of nitrogen, this variation being dependent on the condition of the agricultural year and the time of fertilization.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%